The restorative potential of coastal walks and implications of sound. (1st January 2021) - Nicolosi, Vincent; Wilson, Jackson; Yoshino, Aiko; Viren, Paige
Abstract: A growing body of research suggests blue spaces (oceans and freshwater) can be restorative environments and that sound can influence a restorative experience. This study uses a random cross-over field experiment to compare the perceived restorative outcomes from a coastal and urban walk ( n  = 63) and measures the impact sound (quality, level, type) might have on a participant's restorative experience. Self-reported sound (quality, level, type) explained most of the variation in perceived restoration between the two environments. This study builds on previous findings by providing experimental evidence that blue spaces can be restorative environments and that sound may influence a restorative experience. The findings suggest that blue spaces should be more fully accounted for in restorative environment studies, especially given the large number of people that live by or travel to coastal environments for recreational and leisurely enjoyment.